Angry Birds animal eggventures : join the Angry Birds on a "round the world adventure in search of their stolen eggs" - Esbaum, Jill (National Geographic, 2012)
"Help! The Angry Birds have lost their precious eggs - and they need YOU to find them. Scattered across the globe, you'll have to search the grasslands of Africa, the roaring seven seas, dense rainforests, Australian outback and chilling polar arctic. How, do you ask, will I do it? With the help of your favorite Angry Birds characters readers learn about five different habitats by pairing the eggs found throughout the book with their original region. Kids will also learn about the diverse range of egg-producing animals, everything from fish to amphibians to mammals. Packed with learning exercises and fun activities, this book will transform kids into explorers and leave them wanting more adventure"--